Penerapan Pendekatan Saintifik Dalam Meningkatkan Hasil Belajar Siswa - Nining Tri Wahyuni; Ngarifin Shidiq (Lembaga Pendidikan Hikmatun Najah (LPHN) Blora, 2023)
This modern world, active learning in the classroom is very important for students' creativity. Creativity clearly must be taught with an interesting educational experience to provide satisfactory learning outcomes. The aim of the research is to distinguish between students whose learning outcomes increase when a scientific approach is used and those who do not. Quantitative approach to the experimental method in this study with the conclusions are; 1) Learning outcomes increased with a scientific approach obtained from the gain test results which were 0.52, meaning the success rate was moderate because the gain test results were 0.3 g 0.7. While the control class gain test results of 0.37 means the success rate is moderate, but lower than the experimental class; 2) The results of the calculation show that there is an effect of the scientific approach in the experimental class and those who do not use it in the control class. This can be seen from the results of the hypothesis testing showing that tcount (2.60) ttable (2.01) dk 25 and a significant level of 5% is 2.01. Ha reads